Two GTPase isoforms, Ypt31p and Ypt32p, are essential for Golgi function in yeast. - Benli, M (1996)
In eukaryotic cells, monomeric GTPases of the Ypt/Rab family function as regulators at defined steps of vesicular transport in exo- and endocytosis. Here we report on the isolation and characterization of two genes (YPT31 and YPT32) of the yeast Saccharomyces cerevisiae which encode members of the Ypt family exhibiting >80% sequence identity. Whereas the disruption of one of the two genes was phenotypically neutral, the disruption of both YPT31 and YPT32 led to lethality. Depletion of wild-type Ypt31p or of a short-lived ubiquitin-Ypt31p in a ypt32 null background led to a massive accumulation of Golgi-like membranes, an inhibition of invertase secretion and defects in vacuolar protein maturation. Similar alterations were observed in a conditional-lethal ypt31-1 mutant at 30 min after shift to the non-permissive temperature. According to subcellular fractionation, a significant part of Ypt31p appeared to be located in Golgi-enriched membrane fractions. In accordance with this, indirect immunofluorescence using affinity-purified anti-Ypt31p antibodies gave a punctate staining similar to that observed with Golgi-located proteins. From the phenotypic alterations observed in ypt31 and ypt32 mutants, it seems likely that the two GTPases are involved in intra-Golgi transport or in the formation of transport vesicles at the most distal Golgi compartment.